Keabsahan Kontrak Elektronik dalam Hukum Perdata Indonesia: Tantangan dan Perlindungan Hukum - Sendi Sanjaya; Irene Puteri Alfani Sofia Sinaga (Universitas Suryakancana, 2026)
he development of digital technology has driven the growth of transactions based on electronic contracts, which raise civil law issues related to validity and the protection of the parties involved. Electronic contracts have the potential to create legal uncertainty if adequate regulations are not in place. This study aims to analyze the validity of electronic contracts under Indonesian civil law and to identify forms of legal protection for the parties involved. This research employs a normative juridical method with statutory and conceptual approaches. The results show that electronic contracts can fulfill the legal requirements of a valid agreement as stipulated in Article 1320 of the Indonesian Civil Code, as long as they meet the elements of consent, legal capacity, a specific subject matter, and a lawful cause, with adaptations to the digital medium. Legal protection for parties in electronic contracts is provided through the Electronic Information and Transactions Law (ITE Law) and its implementing regulations, which ensure the authenticity of electronic documents and digital signatures